2017
DOI: 10.1002/hep.29419
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of health risk behaviors to excess mortality in American adults with chronic hepatitis C: A population cohort‐study

Abstract: In resource-rich countries, chronic hepatitis C (CHC) infection is associated with a sizeable excess mortality risk. The extent to which this is due to (1) the biological sequelae of CHC infection versus (2) a high concomitant burden of health risk behaviors (HRBs) is unclear. We used data from the 1999-2010 U.S. National Health and Nutritional Examination Surveys (NHANES), which include detailed information on HRBs and CHC infection status. We calculated the prevalence of the five major HRBs-alcohol use; ciga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…The above differential finding—vis-à-vis a 51% reduction among those with chronic HCV either currently or in the past vs 67% reduction among those with chronic HCV currently—was anticipated. Previous work has shown that heavy alcohol use, as well as other health risk behaviours known to accelerate liver disease progression, are prevalent in HCV-infected populations both in Scotland and elsewhere, and may compromise the clinical benefit of DAAs 20 24 30. New DC presentations among those who had cleared HCV from therapy almost doubled from 15 in 2014 to 27 in 2018; 64% of the latter had an alcohol-related admission history.…”
Section: Discussionmentioning
confidence: 99%
“…The above differential finding—vis-à-vis a 51% reduction among those with chronic HCV either currently or in the past vs 67% reduction among those with chronic HCV currently—was anticipated. Previous work has shown that heavy alcohol use, as well as other health risk behaviours known to accelerate liver disease progression, are prevalent in HCV-infected populations both in Scotland and elsewhere, and may compromise the clinical benefit of DAAs 20 24 30. New DC presentations among those who had cleared HCV from therapy almost doubled from 15 in 2014 to 27 in 2018; 64% of the latter had an alcohol-related admission history.…”
Section: Discussionmentioning
confidence: 99%
“…While most participants reported low or moderate levels of alcohol use, approximately 16% reported heavy use, according to AUDIT-C criteria [22], and this pattern remained consistent throughout follow-up. Among people with chronic hepatitis C, heavy alcohol use has been linked to excess mortality [32].…”
Section: Figurementioning
confidence: 99%
“…Substance abuse disorders have frequently been cited as potential drivers of morbidity and mortality for patients with HIV and/or HCV infection [ 26 , 27 ]. Opioid abuse in high-income countries like the US, in particular, has been associated with a higher disease burden related to HIV and HCV [ 26 ].…”
Section: Discussionmentioning
confidence: 99%